Estimation of lead levels in human blood and marshes water in south of Iraqi - Al-Rekabi, Abdel Ameer Naser (Iraqi Journal of Cancer and Medical Genetics, 2013)
One hundred- eight of water samples have been collected from six stations in Al-Hammar marshes in the period between 18th till 24th of Aug in 2007. In addition ninety-seven of blood has been collected from marsh’s inhabitants who are living and using the marsh water. Lead level has been detected in both water and blood samples by using flame and flameless atomic absorption respectively, the results showed that most samples of water and blood were contained lead levels higher than the acceptance level mentioned by WHO.